Misaligned Expectations and Non-Cooperative Behavior in Indian Microfinance: Evidence from a Survey. Issue 1 (2nd January 2019) - Panda, Debadutta Kumar
Abstract: This study examined the causalities of non-performance of self-help groups (SHGs) in the context of polarised institutional expectations in the microfinance ecosystem in India. Institutional approach and stakeholder approach were followed for the investigation. Focus group discussions (FGDs) and semi-structured interviews (SIs) were conducted to collect data from various institutional stakeholders. It was found that the institutional expectations of each institution from other institutions in the microfinance ecosystem were polarized, misaligned and were antagonistic in nature. Institutional behaviours were governed by their expectations from the microfinance ecosystem. Therefore, the polarized and antagonistic expectations created non-cooperative behaviours and attitudes in the key institutions, which further created a weak performance of the microfinance programs.